Impact of endolymphatic hydrops on DPOAE in subjects with normal to mild hearing loss. Issue 1 (25th December 2022) - Inagaki, Kei; Yoshida, Tadao; Kobayashi, Masumi; Sugimoto, Satofumi; Fukunaga, Yukari; Hara, Daisuke; Naganawa, Shinji; Sone, Michihiko
Abstract: Objective: The increased endolymph volume affects a shift in the organ of Corti and basilar membrane in ears with endolymphatic hydrops (EH), which might affect distortion‐product otoacoustic emissions (DPOAE) by altering the operating point of the outer hair cells. We investigated how changes in DPOAE are related to the distribution site of EH. Study Design: Prospective study. Methods: Among 403 patients with hearing or vestibular symptoms who underwent contrast‐enhanced magnetic resonance imaging (MRI) for the diagnosis of EH and subsequent DPOAE testing, subjects whose hearing levels on pure tone audiometry were ≤35 dB at all frequencies were included in this study. In patients with EH on MRI, the presence and amplitude of DPOAE were evaluated between groups with hearing levels of ≤25 dB at all frequencies versus hearing levels of >25 dB at one or more frequencies. Results: There were no differences in the distribution of EH between groups. The amplitude of DPOAE had no clear correlation with the presence of EH. However, in both groups, there was a significantly higher probability of the presence of a DPOAE response from 1001 to 6006 Hz in cases with EH in the cochlea. Conclusion: Among patients whose hearing levels were ≤35 dB at all frequencies, better responses on DPOAE testing were found in subjects with EH in the cochlea. Alteration of DPOAEs in the early stages of hearing impairment could indicate morphological changes in the inner ear with altered basilar membrane compliance due to EH. Level of Evidence: 4 Abstract : We investigated the impact of endolymphatic hydrops on DPOAE in subjects with normal to mild hearing loss. The characteristics of DPOAE responses in the early stages of hearing disturbances might indicate environmental changes in the inner ear with altered basilar membrane compliance due to EH.